Rancang Bangun Sistem Informasi Manajemen Keuangan Sekolah - Habib, Ahmad; Kindhi, Berlian Al (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2018)
School financial data processing if done manually then the result is less effective. So required financial information management information system to improve the quality of service to students and accelerate the performance of employees in school. It is expected that this system can improve the performance of employees or teachers in school including chairman institutionalized in making decisions. The purpose of this study is to make school financial management information system designed and built by using PHP programming language and MySQL database so that it can process the school finance data such as tuition fee payment and making financial reports done efficiently and effectively. In this study, the author uses two methods, namely data collection methods and methods of system development. For data collection method, we use three way, that is observation, interview and study of library for development of system method used by writer that is incremental method having 5 stages, that is communication, planning, modeling, construction, deployment.